Increased plasma CgA levels associated with nonalcoholic fatty liver disease - Wu, Peng-Bo; Deng, Yin-Zhi; Shu, Yong-Xiang; Tan, Shi-Yun; Li, Ming; Fang, Guo (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: Chromogranin A (CgA), a major soluble protein released by the neuroendocrine system, functions as a prohormone by giving rise to several biologically active peptides. Our study aimed to evaluate the relationship between CgA levels and nonalcoholic fatty liver disease (NAFLD). Materials and Methods: In total, 111 NAFLD patients and 120 healthy controls were enrolled in the trial. The levels of plasma CgA were quantified by an available enzyme-linked immunosorbent assay kit. Pearson’s correlation analysis was conducted to detect whether CgA levels correlated with oxidative stress, insulin resistance, and inflammation profile. A multiple stepwise regression model was used to explore independent determinants for plasma CgA levels. Multivariate logistic regression analysis was conducted to assess whether CgA levels were independent predictors of NAFLD. Results: The levels of plasma CgA between the case and control groups were significantly different (70.9±8.1 μg/L vs 47.6±11.3 μg/L). The levels of plasma CgA positively correlated with high-sensitivity C-reactive protein (hs-CRP; p=0.000), fasting blood glucose (FBG; p=0.025), homeostasis model assessment of insulin resistance index (HOMA-IR; p=0.012), and malondialdehyde (MDA; p=0.037) levels, but negatively associated with superoxide dismutase (SOD; p=0.041) levels. The multiple stepwise regression model indicated that hs-CRP, MDA, and HOMA-IR were independent determinants for plasma CgA levels. The logistic regression analysis showed that plasma levels of CgA were independent predictors of NAFLD. Conclusion: Increased plasma CgA levels were associated with NAFLD.